Fifty years of Quaternary palynology in the Tibetan Plateau - Tang, Lingyu（唐领余）; Shen, Caiming; Lu, Houyuan; Li, Chuanhai; Ma, Qingfeng (Science China Earth Sciences, 2021)
Quaternary palynology in the Tibetan Plateau (TP) was initiated in the 1960s to meet the needs of economic development in western China. Pollen analysis was conducted for the first time on a 200-m long core of Quaternary lacustrine sediments taken from the main body of the TP in order to study pollen assemblages as well as vegetation and climate changes of glacial (cold)/interglacial (warm) periods. Pollen analysis of alpine snow and ice began at the first scientific expedition to the TP in the 1970s. After the 1980s, a series of international collaborative programs were carried out under Sino-French, Sino-German, Sino-Australian, and Sino-American cooperation, marking the integration of Chinese Quaternary palynology society with the international community. New methods for Quaternary palynology were gradually promoted and applied, changing the vegetational and climatic interpretation of Quaternary palynology from qualitative to quantitative. Since the 1990s, many palynologists have carried out extensive Quaternary palynological studies on fossil pollen sites of more than 60 lakes/sections and alpine glaciers in the TP to discuss the spatiotemporal vegetation changes and climatic and environmental evolution of the TP since the Pleistocene. Over the past half-century, Quaternary palynology in the TP has contributed to the establishment of the Chinese Quaternary pollen database and the study of vegetation and climate evolution since the Last Glacial Maximum (LGM) in the TP. Currently available pollen records revealed the spatial and temporal distribution of vegetation in the TP since the LGM, exhibiting expansions and shrinkages of forest, meadow, grassland and desert in different periods such as the LGM, the last deglaciation, and Holocene optimum period. The paleomonsoon reflected by paleovegetation since the LGM has undergone the changes of weak-strengthening-strong-weakening but still active-shrinking, which is mainly affected by solar insolation.